Infected delayed puerperal hematoma complicated by retention of urine: a case report and literature review - Ratsiatosika, Tanjona A.; Romuald, Randriamahavonjy; ., Faisoaly; Lantonirina, Rainibarijaona A.; Martial, Rakotonirina; Ando-Miora, Rakotonirina; Rakotovao, Andrianampanalinarivo H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The puerperal hematoma corresponds to a tissue cleavage, most often paravaginal or vulvar, in which the vascular wounds, linked to the detachment, have no spontaneous tendency to haemostasis. The aggravation of this pathology is progressive. Diagnosis and management must be an obstetric emergency. Author report a case of infected puerperal hematoma complicated by rectal compression and acute retention of urine. This is a 26-year-old patient with a history of chronic hypertension. Labor was induced by misoprostol. The delivery was uneventful at 37 weeks vaginally. Ten days after delivery, she returned to the obstetrical emergency service for acute urine retention. The examination with the vaginal speculum showed a tumefaction of six centimeters on the left lateral side of the vagina. Surgical treatment has been performed. The suite was without particularity. The diagnosis of puerperal hematoma must be early. Even for the delayed form, the complications are identical. Blood loss, compression of proximity organs and infection are the most common complications. The care must be multidisciplinary. Resuscitation of the patient associated with haemostasis of the vessel is the main treatment in cases of large hematoma with hemodynamic instability.